YENİÇERİ KOYU MONOGRAFİSİ. - TOPSES, Mehmet Devrim (Electronic Turkish Studies)
Village monographs are scientific researches which help to identify the possible factors that influence the social changes. In the sociology literature, theoretical and applied researches focusing on the social structure of the villages show that the economic diversity and cultural interaction processes can be considered among the determinant factors which affect the social structure. The aim of this research is to explain the social structure in Yeniçeri village which is connected to Çan county, in relation with the economical and geographical parameters. Yeniçeri village is the closest dwelling unit to the center of Çan in comparison with the other villages in the neighborhood. There is an extensive range of transportation opportunities between the town center and the village. The nearness of the village to Çanakkale Ceramics Factory and the existence of an active mine in territory, have changed the culture from agrarian to industrial and the people from villager to factory workers. In relation with the economic and social conditions as such, the topics of this research have been the religiousity, the fatalistic world view of the people; together with the social position of the woman in the village and the cooperation among the families and the relatives. In this research, the techniques of observation, interview and survey have been used, the collected data have been transmitted into frequency chart by using SPSS(Statistical Package for the Social Sciences) 16.0 program. Findings of the research may be stated in the following: that the rate of religiousity has decreased despite the prevailing common fatalistic world view; that there is a homogeneity and maintanence of the Islamic religious practices, and that religious practices are not the criteria for political judgements; and consequently that the women are located in more or less the same social positions with those in the urban areas in terms of the division of property and their familial responsibilities. Comparative village monographs are needed to be made in order to determine the possible relationship between the social structure of Turkey and economic and geographic variables.